Induction of Parturition using Mifepristone and Misoprostol in Bitch with Single Pup Syndrome - Kumar, Keshav; Sengupta, Dipyaman; Sheetal, Shailendra Kishore; Azad, Chandra Shekhar (The Indian Journal of Animal Reproduction, 2023)
Single puppy syndrome is common in older bitch. It occurs mostly due to the death of embryos during early gestation and resorption before mineralization. A two-year-old Labrador bitch in her first parity was presented to the Veterinary Clinical Complex, Bihar Veterinary College, BASU, Patna with the history of breeding approximately 72 days ago. A lateral abdominal radiograph revealed single fully-grown fetus with anterior presentation in uterus. The bitch was treated with mifepristone and misoprostol for three days. After three days of treatment, bitch delivered a dead fetus and recovered uneventfully.